2016
DOI: 10.1093/gbe/evw036
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Phylogenetic Analysis Sheds Light on the Diversity and Origin of the MLO Family of Integral Membrane Proteins

Abstract: Mildew resistance Locus O (MLO) proteins are polytopic integral membrane proteins that have long been considered as plant-specific and being primarily involved in plant–powdery mildew interactions. However, research in the past decade has revealed that MLO proteins diverged into a family with several clades whose members are associated with different physiological processes. We provide a largely increased dataset of MLO amino acid sequences, comprising nearly all major land plant lineages. Based on this compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
133
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(148 citation statements)
references
References 87 publications
14
133
0
Order By: Relevance
“…The data presented there for the Arabidopsis MLO genes are in agreement with our findings (Additional file 2), as they report that in most tissues the major MLO S-gene AtMLO2 is much higher expressed than the other two clade V MLO genes [42]. Rice has two clade IV MLO genes, OsMLO3 and OsMLO6 [25] , it was found that in most rice tissues OsMLO3 transcription was much higher than OsMLO6 transcription [42]. Based on this finding, the authors conclude that OsMLO3 is likely to be the major clade IV MLO in rice, rather than OsMLO6 .…”
Section: Discussionsupporting
confidence: 90%
“…The data presented there for the Arabidopsis MLO genes are in agreement with our findings (Additional file 2), as they report that in most tissues the major MLO S-gene AtMLO2 is much higher expressed than the other two clade V MLO genes [42]. Rice has two clade IV MLO genes, OsMLO3 and OsMLO6 [25] , it was found that in most rice tissues OsMLO3 transcription was much higher than OsMLO6 transcription [42]. Based on this finding, the authors conclude that OsMLO3 is likely to be the major clade IV MLO in rice, rather than OsMLO6 .…”
Section: Discussionsupporting
confidence: 90%
“…The biochemical function of MLO proteins remains unknown (Acevedo‐Garcia et al, ; Kusch et al, ). Here, we demonstrate that clade V MLOs act, in unequal genetic redundancy, as negative regulators of ROS signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Mildew Locus O ( MLO ) genes code for polytopic integral membrane proteins of unknown biological function (Acevedo‐Garcia, Kusch, & Panstruga, ). Mlo was originally identified in barley ( Hordeum vulgare ) but is conserved in plants in small to medium‐sized gene families (Büschges et al, ; Kusch, Pesch, & Panstruga, ). Loss‐of‐function alleles of specific MLOs confer resistance against powdery mildew disease in various plant species; thus, they are considered negative regulators of plant immunity or alternatively as “susceptibility” genes co‐opted by powdery mildew pathogens to promote pathogenesis (Panstruga, ; van Schie & Takken, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MLO genes are characterized by 7 transmembrane helices, similar to metazoan and fungal G-protein coupled receptors [13]. All the MLO susceptibility genes in clade V share highly conserved domains within transmembrane portions of the protein and harbor a four amino acid long motif at the C-terminus that has been associated with PM interaction [14].…”
Section: Introductionmentioning
confidence: 99%